Обобщенная математическая модель процедуры ситовой классификации порошков сверхтвердых материалов - Петасюк, Г.А. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2007)
We propose method of indirect determination of grain size and grain size distribution of SHM grinding powders without control sieve analysis standard procedure. The method is based on mathematical simulation of sieve analysis procedure and application of microscopic analysis data.The results of method testing for standard grinding powders of synthetic diamond are presented.